The Value of Neighborhood and Property Tree Canopy Across Different Property Values for Residential Resales in San Antonio, Texas - Ryun Jung Lee; Thomas A. Thomson (Journal of Sustainable Real Estate)
Previous research shows that neighborhood trees promote housing premiums, but property tree may not. This paper expands the research by measuring the value that property and neighborhood tree canopy add to home sale price. Rather than treating the entire city as the analysis area, we break the city into four Areas based on average house selling price and evaluate the canopy results by Area. We employ the 1 m resolution tree canopy data from the 2017 LiDAR, from which we extract the percentage of tree canopy on each property, and the percentage of tree canopy for the block group in which the sale took place (which we use as our neighborhood measure). We employ a semi log hedonic pricing model to analyze about 41,500 existing home sales to estimate the value of tree canopy. Our results show that in the Area with the lowest property values, either higher or lower than median tree canopy results in properties selling for less than the average canopy. For more valuable Areas, having less than median tree canopy generally reduces sale value while having more than median canopy increases sale value. We find this generally holds for both property canopy, and neighborhood canopy.